PENGARUH MINAT BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 4 SIGI - Silfitrah Silfitrah; Wahyuni H Mailili (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This study aims to determine the effect of learning interest and learning motivation on students' cognitive learning outcomes in set material in Sigi 4 Public Middle School. The type of research used is expost factod with a population of all seventh grade students of SMP Negeri 4 Sigi which were registered in the 2017/2018 school year with 248 students. Technic sampling that is simple random sampling so the sample size was106 students.The data collection methods are questionnaire, documentation, and test methods.Analysis of the data using the product moment correlation test then followed by multiple regression tests .The results obtained by double linear regression were Y = 7.478 + 0.086 X₁ + 0.091X₂ . Based on the results of research and discussion of data analysis concluded that: (1) There is significant influence between interest in learning the learning outcomes of the mathematics class VII SMP Negeri 4 Sigi with